Purification and chemical characterization of antigens from sheep erythrocytes - Tucková, L (Folia microbiologica, 1979)
A mixture of glycoproteins and glycolipids was solubilized from sheep erythrocytes membranes under the effect of high ionic strength (2 M NaCl, 0.5 M Tris). Several antigenic fractions could be purified from the mixture using gel filtration on Sephadex G-200 and block electrophoresis on Pevikon C870; two fractions were found to raise antibodies in a primary reaction and these antibodies effectively sensitized erythrocytes to lysis by complement. The majority of other fractions elicited a weaker primary reaction which was detectable by both agglutination and haemolysis. The fraction, migrating fastest towards the cathode, elicited after immunization a formation of antibodies that could be detected almost exclusively by haemagglutination. The fraction, which elicited in the primary reaction a high titre of haemolytic antibodies, is composed of 72% proteins, 11% lipids and 15% saccharides.
Keywords: Animals; imunoelektroforéza; sacharidy; Hemagglutination Tests; Immunoelectrophoresis; erytrocyty; Antibody Formation; hemolýza; lipidy; ovce; Antigens; antigeny; Chromatography, Gel; Mice; tvorba protilátek; Antibodies; Carbohydrates; Lipids; Electrophoresis; myši; elektroforéza; Blood Proteins; krevní proteiny; hemaglutinační testy; Erythrocytes; Sheep; Hemolysis; gelová chromatografie; zvířata; protilátky